Love and Distance: Unveiling the Influence of Self-Disclosure, Gratitude, and Marital Satisfaction Among Military Wives - Pratiwi, Nuke Aulia; Mukhoyyaroh, Tatik (Jurnal Psikologi Terapan, 2024)
This study examines the influence of self-disclosure and gratitude on marital satisfaction among military wives in long-distance marriages (LDM). Long-distance relationships present challenges in communication and emotional intimacy, making marital satisfaction highly dependent on open communication and the ability to appreciate ones partner. This study aims to determine the extent to which self-disclosure and gratitude contribute to marital satisfaction among military wives in Surabaya. This research employs a quantitative correlational approach, involving 350 military wives in long-distance marriages. Data were collected using a Likert-scale questionnaire, including the ENRICH Marital Satisfaction Scale (EMS) for marital satisfaction, the Revised Self-Disclosure Scale (RSDS) for self-disclosure, and the Gratitude Questionnaire-6 (GQ-6) for gratitude. Multiple regression analysis was conducted to examine the influence of each variable on marital satisfaction. The findings indicate that self-disclosure has a positive impact on marital satisfaction. Wives who openly share their thoughts and feelings with their spouses tend to experience greater harmony in their relationships. Gratitude also plays a significant role, as individuals who appreciate their partners are more likely to feel happiness and fulfillment in their marriage. Together, these two variables make a substantial contribution to marital satisfaction among military wives in long-distance marriages. In conclusion, this study highlights that open communication and gratitude are essential factors in maintaining harmony and happiness in long-distance marriages. Therefore, couples in LDM are encouraged to improve open communication and cultivate gratitude to navigate the challenges of their relationship successfully.